(untitled) (Mustansiria Dental Journal, 2005)
Mouth breathing is associated with many dental and facial problems and thought of as having a bad effect on orthodontic treatment . The aim of this study was to study the effect of mouth breathing on SNA angle maxillary incisor to SN angle and dental arch dimensions. And to compare these values with those of nasal breathers. A study sample of 17 mouth breathers were compared with 17 nasal breathers. Results showed for the mouth breather’s very small increase in SNA angle with marked proclination of upper incisors, and constriction of upper arch which is more in the posterior segment .